Germanium electron–hole bilayer tunnel field-effect transistors with a symmetrically arranged double gate. (3rd March 2015) - Jeong, Woo Jin; Kim, Tae Kyun; Moon, Jung Min; Park, Min Gyu; Yoon, Young Gwang; Hwang, Byeong Woon; Choi, Woo Young; Shin, Mincheol; Lee, Seok-Hee
Abstract: A germanium tunnel field-effect transistor (TFET) with a bias-induced electron–hole bilayer (EHB) with double gates that are symmetrically arranged and independently biased is simulated. The symmetric double gate scheme is feasible, presenting a simple EHB-TFET structure that is practicable for industrial fabrication. According to simulation results, the improvement of on/off current ratio of ∼10 8 is achieved by inserting a lightly-doped drain-source (LDD) region. Also, fin-type EHB-TFETs show an extremely low average sub-threshold swing of 11 mV/decade over 4 decades at V DD = 0.5 V, and thus are suitable for ultra-low power applications.